Perlindungan Hukum Anak Korban Tindak Pidana Eksploitasi Seksual dalam Perspektif Kepastian Hukum - Firda Yunita Dewi; Y.A Triana Ohoiwutun; Ainul Azizah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The cases of child sexual exploitation continue to rise in Indonesia. However, the legal system has yet to provide legal certainty for children as victims. This study aims to examine the positive legal framework regarding the protection of child victims of sexual exploitation, assess its implementation in providing legal certainty, and offer an ideal concept of legal protection for the future. The method used is normative juridical with statutory, case, and conceptual approaches. The results show that although legal instruments such as the Child Protection Law, the Sexual Violence Crime Law, and regulations related to restitution are in place, their implementation remains ineffective. Restitution rights are often not pursued due to victims’ lack of awareness and weaknesses in the legal system. This study recommends that restitution be granted automatically and that the role of law enforcement be strengthened to ensure the protection of children's rights.